(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article explores the development of cultural diplomacy within the Organization of Turkic States, established in 2009 and renamed in 2021. Employing Joseph Nye’s soft power concept and constructivist international relations theory, it examines how member states utilize shared history, language, and culture to strengthen regional cohesion and Eurasian influence. Key institutions like TÜRKSOY, the International Turkic Academy, and the Turkic Culture and Heritage Foundation drive initiatives such as joint UNESCO heritage listings, Cultural Capitals designations, and diaspora engagement. Aligned with the Turkic World Vision 2040, these efforts enhance collective identity, regional stability, and global visibility while addressing geopolitical challenges. The article evaluates mechanisms, achievements, and limitations of this identity-driven diplomacy in contemporary regional organizations.